Natural Products for the Prevention and Treatment of Common Cold and Viral Respiratory Infections - Nour Mammari; Quentin Albert; Marc Devocelle; Maša Kenda; Nina Kočevar Glavač; Marija Sollner Dolenc; Laura Mercolini; Jaroslav Tóth; Nagy Milan; Szilvia Czigle; Mihayl Varbanov; on behalf of the OEMONOM (MDPI AG, 2023)
The common cold is generally considered a usually harmless infectious disease of the upper respiratory pathway, with mostly mild symptoms. However, it should not be overlooked, as a severe cold can lead to serious complications, resulting in hospitalization or death in vulnerable patients. The treatment of the common cold remains purely symptomatic. Analgesics as well as oral antihistamines or decongestants may be advised to relieve fever, and local treatments can clear the airways and relieve nasal congestion, rhinorrhea, or sneezing. Certain medicinal plant specialties can be used as therapy or as complementary self-treatment. Recent scientific advances discussed in more detail in this review have demonstrated the plant's efficiency in the treatment of the common cold. This review presents an overview of plants used worldwide in the treatment of cold diseases.